Environmental Factors Associated with Chinese Older Immigrants' Social Engagement. (12th August 2019) - Lai, Daniel W.L.; Li, Jia; Lee, Vincent W.P.; Dong, XinQi
Abstract : BACKGROUND/ OBJECTIVES: Prior research has shown that social engagement is beneficial to older adults' health and well‐being. This study examined the association between environmental factors and social engagement of older Chinese immigrants in the United States. SAMPLE: A cross‐sectional data set of Chinese immigrants in the greater Chicago, IL, area (Population Study of Chinese Elderly; n = 3159), was used in this study. DESIGN: Multiple regression models were used to test the associations between older adults' engagement in cognitive and social activities and environmental factors, including financial difficulties, social support, neighborhood cohesion, neighborhood disorder, and sense of community. MEASUREMENT: Eight questions measuring participants' engagement in cognitive and social activities, a single‐item question measuring financial difficulties, a 12‐item social support measurement, an eight‐item neighborhood cohesion measurement, and a six‐item neighborhood disorder and sense of community scale. RESULTS: Having fewer financial difficulties and a cohesive neighborhood is related to a higher level of engagement in both cognitive and social activities. More social support from family and friends and a sense of community are associated with higher levels of social activities engagement, but not cognitive activity engagement. Neighborhood cohesion has a stronger association with social engagement than other environmental factors and most individual‐level factors. Surprisingly, neighborhood disorder is positively related to social activity engagement, which needs further examination. The associations between environmental factors and social engagement showed no significant difference between healthy and unhealthy older adults. CONCLUSION: This study highlights the need for policies and programs to promote an active lifestyle among older immigrants by creating facilitative social and physical environments. J Am Geriatr Soc 67:S571–S576, 2019.